Extracellular biosynthesis of bimetallic Au-Ag alloy nanoparticles - Senapati, S.; Ahmad, Absar; Khan, Mohammad Islam; Sastry, M.; Kumar, R. (Small, 2005)
Keywords: alloys; Biosynthesis; composites; enzymes; Nanoparticles

Effect of gold dispersion on the photocatalytic activity of mesoporous titania for the vapor-phase oxidation of acetone - Awate, S. V.; Belhekar, Anagha A.; Bhagwat, S. V.; Kumar, R.; Gupta, N. M. (International Journal of Photoenergy, 2008)
Mesostructured titanium dioxide photocatalyst, having uniform crystallite size (6-12 nm) and average pore diameter of similar to 4.2 nm, was synthesized by using a low-temperature nonsurfactant hydrothermal route, employing tartaric acid as a templating agent. Gold additions from 0.5 to 2wt% were incorporated, either during the hydrothermal process or by postsynthesis wet impregnation. Compared to the impregnation-prepared samples, the samples synthesized hydrothermally contained smaller-size (<= 1 nm) gold clusters occluded in the pores of the host matrix. Whereas CO(2) and H(2)O were the main reaction products in UV-assisted vapor-phase oxidation of acetone using these catalysts, C(2)H(6) and HCO(2)CH(3) were also produced for higher acetone concentrations in air. The conversion of acetone was found to increase with decrease in the size of both TiO(2) and gold particles. In situ IR spectroscopy revealed that titania and gold particles serve as independent adsorption and reaction sites for acetone and oxygen molecules. Acetone molecules adsorb exclusively at TiO(2) surface, giving rise to a strongly adsorbed (condensed) state as well as to the formation of formate- and methyl formate- type surface species. Hydroxyl groups at titania surface participate directly in these adsorption steps. Nanosize gold particles, on the other hand, were primarily responsible for the adsorption and activation of oxygen molecules. Mechanistic aspects of the photochemical processes are discussed on the basis of these observations. Copyright (C) 2008.

Effect of protonation and deprotonation on electron transfer mediated decay and interatomic coulombic decay - Kumar, R.; Vaval, N. (ChemPhysChem, 2023)
Electronically excited atoms or molecules in an environment are often subject to interatomic/intermolecular Coulombic decay (ICD) and/or electron transfer mediated decay (ETMD) mechanisms. A few of the numerous variables that can impact these non-radiative decay mechanisms include bond distance, the number of nearby atoms or molecules, and the polarisation effect. In this paper, we have studied the effect of protonation and deprotonation on the ionization potential (IP), double ionization potential (DIP), and lifetime (or decay width) of the temporary bound state in these non-radiative decay processes. We have chosen LiH-NH3 and LiH-H2O as test systems. The equation of motion coupled cluster singles and doubles method augmented by complex absorbing potential (CAP-EOM-CCSD) has been used in calculating the energetic position of the decaying state and the system's decay rate. Deprotonation of LiH-NH3/LiH-H2O either from the metal center (LiH) or from ammonia/water lowers the IP and DIP compared to the neutral systems. In contrast, protonation increases these quantities compared to neutral systems. The protonation closes the inner valence state relaxation channels for ICD/ETMD. For example, the decay of the O-2s/N-2s state stops in protonated systems (LiH2+-H2O, LiH2+-NH3, and LiH-NH4+). Our study also shows that the efficiency, i. e., the rate of ICD/ETMD, can be altered by protonation and deprotonation. It is expected to have implications for chemical and biological systems.